Traumatic Perforation of Tympanic Membrane: A Rural Profile of Bangladesh (Medicine Today, 2017)
To determine the various etiological factors, clinical presentation and outcome of traumatic perforation of tympanic membrane (TM) in a rural area of Bangladesh. A retrospective study of 210 cases of traumatic perforation of TM in upazilla health complex, Nangalkot and Muradnagar, Comilla, Bangladesh within the period of March 2013 to February 2014. The study showed middle age people of 20-39 years age group were mostly affected (61.89%), where males are more than females at the ratio of 1.18:1. Domestic violence was a major factor (50%) and husbands are only culprit for 35.13% of housewives and slap was the major mode of injury (52.86%) affecting the left ear mostly (70.95%). Spontaneous healing rate was very satisfactory and it was 88% within 03 months in our study. Traumatic perforation of TM is a common type of injury in rural areas. Unnecessary surgical intervention or unskilled handling should be discouraged. Early appearance and watchful treatment reduces the morbidity.Medicine Today 2016 Vol.28(2): 79-82